113 Implementing video consultations in a UK hospice during the Covid-19 pandemic: learning from healthcare professionals' feedback. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Milne, Shannon; Palfrey, Jennifer; Berg, Jane; Todd, Jennifer
Abstract : Introduction: Providing care for our patients, carers and families during the coronavirus pandemic required a rapid shift to remote consultations, using videoconferencing technology. A service evaluation was performed to capture hospice professionals' experience. Methods: An online survey exploring experience and satisfaction was sent to a convenience sample of hospice professionals who had participated in video consultations between March and June 2020. Results: 35 hospice professionals responded, and both quantitative and qualitative data was analysed. 62.5% rated their video consultations as good, despite 94.1% having no prior video consultation experience. A third of respondents had undertaken potentially sensitive consultations, including advance care planning and resuscitation. Although 50% of respondents had undertaken first assessments remotely, they consistently found this more challenging when the patient was not known to them previously. The results helpfully captured specific scenarios, when video consultations were less appropriate. 75% of respondents had undertaken a video consultation with a family member participating and 52.9% had included an external health professional. Wellbeing staff had also successfully provided multiple group support sessions via video for both patients and carers. The respondents thought video consultations were efficient and convenient for hospice professionals (80.6%) and patients (67.7%). As a consequence of the rapid shift to video consultations, our results highlighted that 78% of respondents had received no formal training, and in addition, 39% reported some technical difficulties. Overall 80.7% wanted to offer video consultations as an option in the future. Conclusion: Hospice professionals have quickly adapted to video consultations and are keen to continue to offer this service in the future but need appropriate training and reliable videoconferencing technology in order to do this effectively. Videoconferencing can be used in creative ways to expand access for patients and family caregivers to a range of palliative care services and enhance multi-professional team-working.